Strategi Pengelolaan Sampah Di Pesantren Dayah Darul Ihsan Aceh Besar - Jadidah, Wanti Nur (Jurnal Pengendalian Pencemaran Lingkungan (JPPL), 2025)
Waste is a problem that is constantly being discussed and a solution is sought. Every minute, second we will produce waste, both biodegradable and non-biodegradable. Waste generated from human activities will affect humans and the ecosystem around where they live. The purpose of this study is to find out the waste management strategy implemented at the Dayah Darul Ihsan Islamic Boarding School in Aceh Besar and the obstacles in waste management that exist at the Islamic Boarding School Dayah Darul Ihsan Aceh Besar. The method used in this study is observation and library research. The results of this study indicate that there are already several waste management strategies at the Darul Ihsan Islamic Boarding School, including the application of the 3R concept (Reduce, Reuse, Recycle), making eco bricks from snack waste, sorting waste in the classroom and dormitory environment, and establishing a waste bank. While the obstacles encountered are the lack of synergy from school members, the lack of awareness from each individual to sort waste, and the lack of implementation of integration between learning and caring for the environment. Keywords: 3R concept; environmental education; waste management